Role And Organization of Independent Physical Training of Students of Engineering and Technical University - Abdalimov O.Kh. (Zien Journals, 2022)
The purpose of our study was a theoretical generalization of the features of the contentoperational component of the organization of independent training in physical culture for students of an engineering and technical university
Keywords: engineering; study; purpose; generalization